Penerapan Metode Critical Path Method (CPM) Pada Network Planning Dalam Efisiensi Waktu dan Biaya Proyek Pembangunan Rumah Minimalis (Studi Kasus: Property Group Medan) - NST, Deni Prawira (STMIK Budi Darma, 2020)
Along with developments in the industrial world, as well as property developments, especially in the construction of rapidly increasing homes, the level of difficulty and managing a home project is higher. The higher the level of difficulty, means the longer duration of time needed to complete the project. In a project the longer the duration required, the greater the automatic costs and vice versa if the duration of work needed is small, the costs required are also small. Network planning (network planning) in principle is a dependency relationship between the parts of the work that are described or visualized in a network diagram. The problem with the Property Group in the construction of minimalist houses is that the estimated duration of the project is not timely completion because the data created from the office sometimes does not match the data in the field. To overcome the problem regarding the estimated time in project completion, the Critical Path Method (CPM) method is used. So it is very necessary a time management (Time Management) to streamline the time of a project which in addition to sharpening priorities, also striving to improve the efficiency and effectiveness of project management in order to achieve maximum results from available resources. All of these achieve the goal of a home construction project that is success that meets the criteria of time (schedule) as well as cost (budget) and quality (quality). In addition to time management, of course also must be followed by a good project implementation and in accordance with planning. With good time management and implementation, the risk of a minimalist home construction project will experience a smaller delay.